Evaluation of pretreatment telomere length as a prognostic marker in intermediate‐risk acute myeloid leukemia. (21st July 2021) - Gu, Runxia; Cao, Jingjing; Wei, Shuning; Gong, Xiaoyuan; Wang, Ying; Mi, Yingchang; Zhang, Junping; Qiu, Shaowei; Rao, Qing; Wang, Min; Wei, Hui; Wang, Jianxiang
Abstract: Introduction: The current framework for risk stratification is still insufficient for highly heterogeneous intermediate‐risk acute myeloid leukemia (IRC‐AML), which lacks specific genomic abnormalities. Methods: In order to incorporate novel biomarkers to refine current risk stratification strategies for patients with this subtype, we investigated pretreatment telomere length (TL), which is essential for maintaining genomic stability, in 204 adults with de novo AML (non‐acute promyelocytic leukemia). Results: We found that TL measured at diagnosis did not decrease with advancing age in 204 patients with AML (R 2  = 0.001, P  = .695). A multivariate analysis demonstrated that short TL was independently associated with an inferior relapse‐free survival (hazard ratio [HR] 3.08, 95% confidence interval [CI] 1.48‐6.41, P  = .003); event‐free survival (HR 2.14, 95% CI 1.12‐4.08, P  = .021); and overall survival (HR 2.26, 95% CI 1.09‐4.67, P  = .028) in IRC‐AML patients. In addition, IRC‐AML patients with short TL also exhibited an increased cumulative incidence of hematologic relapse (HR 2.32, 95% CI 1.08‐5.26, P  = .032). Conclusion: Short TL is an independent prognostic factor for poor prognosis in patients with IRC‐AML and may represent a novel mechanism that links genomic stability and disease progression.